PEMBUATAN PROTOTYPE PEMADAM API OTOMATIS BERBASIS ARDUINO UNO R3 - sofyan sofyan; Adhitya Pandu Perdana; Agik Yan Prasetya (Informasi Interaktif, 2016)
The prototype of automatic fire extinguishers that combine this automatic window using an Arduino Uno R3 microcontroller based on ATmega328P chip to detect the presence of fire or high temperature. For the output part the arduino is connected to the LM35 component for temperature guidance, LED Board to display the status and temperature in the prototype, mini water pump for spraying / draining water at the temperature of the boundary and serial boundary connected to the laptop to display the current temperature status.Key words: automatic fire extinguisher, automatic window